Temperature-responsive molecular liquids based on dihydrophenazines for dynamic multicolor-fluorescent anti-counterfeiting and encryption. (3rd February 2021) - Liu, Hao; Song, Wenxuan; Chen, Xuanying; Mei, Ju; Zhang, Zhiyun; Su, Jianhua
Abstract : Multicolor printing, dynamic anti-counterfeiting, and advanced information encryption are conveniently realized by harnessing the temperature-sensitive and dual-emissive molecular liquids based on vibration-induced emission fluorogens. Abstract : Solvent/dopant-free luminescent molecular liquids, as a kind of organic soft material, are very useful and attractive. Herein, the vibration-induced emission (VIE) strategy was exploited to develop the smart non-volatile luminescent materials with dynamic multicolor-fluorescence. In this approach, four dihydrophenazine-based non-volatile luminescent compounds, i.e., DPAC- n ( n = 5, 10, 15, and 20), were facilely developed by covalently attaching long alkyl chains onto the typical VIE-active core, i.e., 9, 14-diphenyl-9, 14-dihydrodibenzo[ a, c ]phenazine (DPAC). The n in DPAC- n represents the alkyl chain length of these DPAC derivatives. Since the complex viscosities of the luminescent molecular liquids decrease as n increases, which was confirmed by the rheological analysis, the intramolecular motions and the fluorescence behaviors are closely correlated with the alkyl chain length. Due to the VIE effect of DPAC, these non-volatile liquid materials exhibit efficient temperature- and viscosity-sensitive dynamic multicolor emission. These luminophores predominantly emit blue fluorescence (FL) at low temperature ( e.g. 20 °C) with high complex viscosity but chiefly orange-red FL at high temperature (85 °C) with low complex viscosity, exhibiting a gradual multicolored fluorescence response to temperature change. The influence of alkyl chain length on the viscosity-dependent luminescent behavior was also systematically investigated and discussed. Because of its lowest complex viscosity, DPAC-20 with the longest alkyl chain shows the most significant temperature-sensing capability. Taking advantage of the above-mentioned unique properties, we have realized the application of solvent/dopant-free luminescent liquids as temperature-sensitive high-performance non-doped fluorescent inks for multicolor printing, advanced encryption and dynamic anti-counterfeiting. Our findings not only expand the application scope of VIE molecules, but also provide powerful materials for information encryption and anti-counterfeiting.